Counselling Children of Divorce: A Divorce Lifeline Program - Hett, Ph.D., Geoffrey G.; Rose, M.A., Christopher D. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper reports the results of three control group studies which examined the efficacy of a group counselling program for children of divorce. These studies were designed to test the hypothesis that the children who participated in the group counselling intervention programs would exhibit less anxiety, greater self-esteem and show improved adjustment to the experience of divorce than would the children in the control groups. In addition, in one of the studies, the experimental subjects were expected to show greater internal orientation than their control groups peers and in another of the studies the experimental subjects were expected to show fewer school-related problems. Significant differences were found between groups in some areas. Differences were not found, however, between groups on measures of anxiety and self-esteem. The reasons for the program's ineffectiveness at changing levels of anxiety and self-esteem are discussed.